THE EFFECT OF USING THE OMETV APPLICATION ON THE SPEAKING ACHIEVEMENT OF 11TH- GRADE STUDENTS AT SMK MARISI MEDAN - Nelinda Kristauli Nasution; Febrina S.L Lumbantobing; Christina Natalina Saragi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to investigate the effect of using the OmeTV application on the speaking achievement of 11th-grade students at SMK Marisi Medan. Speaking is one of the most essential skills in English learning; however, many students face difficulties such as limited vocabulary, lack of fluency, poor pronunciation, and low confidence. To address these issues, OmeTV a video chat platform that connects users worldwide in real-time conversations was used as a learning medium to provide authentic and interactive speaking practice. This study employed a quantitative experimental design using the pre-test and post-test control group method. The population consisted of eleventh-grade students of SMK Marisi Medan, with a total sample of 55 students divided into an experimental group and a control group.